Between Piety and Excess: Cult-Like Behavior in the Al-Shādziliyyah Pondok Pesulukan Thoriqot Agung (PETA) Order - An Najmi, Muhammad Izzul Islam; Al-Ahmad, Ahmad (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study explores community perspectives on Sufi orders, focusing on the al-Shādziliyyah Order of Pondok Pesulukan Thoriqot Agung (PETA) in Tulungagung, East Java. The rapid growth of Sufi movements in Indonesia has given rise to various religious expressions, including strong emotional ties and loyalty to spiritual leaders (mūrshid). In this Order, the emergence of cult-like behavior has raised concerns about the limits of religious reverence and its alignment with Islamic teachings. Using a qualitative approach, this research examines the extent and nature of such behavior and whether it departs from Qur’anic and Hadith principles or remains within accepted Sufi piety. Georg Simmel’s theory of social interaction is employed to analyze how social bonding and charismatic authority contribute to excessive veneration. Data were collected through fieldwork, semi-structured interviews, and literature review. The findings show a range of attitudes among followers, from sincere devotion to problematic loyalty, particularly the belief in the mūrshid’s spiritual infallibility. These patterns are reinforced through ritual practices, group dynamics, and the leader’s perceived charisma. This study contributes to the discourse on contemporary Sufism in Indonesia by highlighting the sociological mechanisms that shape religious authority and group cohesion. It calls for critical reflection within Sufi Order communities to maintain a balance between spiritual guidance and theological boundaries.